Analisa Penerapan Jual Beli Emas untuk Transaksi Top Up - Heryadi, Deny (JUDICIOUS, 2025)
Credit unions have products for disbursing funds, often referred to as financing. Members who apply for financing often do so with the intention of paying off their remaining debts in order to reduce their overall debt or simply to reduce their installment payments. Such applications are permissible and valid, i.e., they are not prohibited under sharia law. However, what concerns us is that the use of the contract is not as straightforward as the cooperative and its members might imagine. There are several aspects that need to be examined and analyzed to ensure the transaction is valid and does not violate Sharia principles. The first objective of this study is to provide a general description of the contracts or transactions that can be used to facilitate top-up transactions in a Sharia-compliant cooperative. Second, this research aims to share information with cooperatives facing similar cases. It is hoped that this presentation will provide an overview and knowledge of the steps that must be taken if one wishes to conduct a top-up financing transaction. The research method used in the preparation of this paper is based on a descriptive analytical research type. The data collection techniques used by the author include field observation, interviews, and documentation. This research is also supported by secondary data from both the company directly and literature (books). This research will discuss how Islamic cooperatives should use the appropriate contract for transactions involving the repayment of old debts without violating Islamic principles. The conclusion of this research is that we must be careful in handling top-up transactions to ensure they do not deviate from Islamic principles.